Agroclimate and Crop Planning in north-easten region - Saikia, U S; Goswami, B (Indian Farming, 2018)
Climatic elements play an important role in plant life. During vegetative stage important elements of consideretion are, moisture stress, radiation and temperature. During reproduction stage elements like day length, annual variation in radiation and temperature etc. play an important role.